Komunikasi Stakeholder pada Kegiatan Kaji Terap Budidaya Padi Toleran Salinitas di BPTP Jawa Barat - Dini Fibriyanti; Sadono, Dwi; Sarwoprasodjo, Sarwititi (Jurnal Penyuluhan, 2021)
The success of the applied study can be achieved if the cooperation and coordination between stakeholder goes well so that there is an acceleration of the spread of innovation and the sustainable adoption of agricultural innovations. The study aims to analyze the correlation between the characteristics of the communication and database media, the characteristics of individual, and the actions of collective and social networks with the effectiveness of stakeholder communication on the applied study of salinity tolerant paddy cultivation. The study was conducted on February-March 2020 in BPTP West Java and Pangandaran Regency. Determination of the respondents carried out by using census method with a total of 33 people. The analysis using Ucinet 6 and rank Spearman correlation test. The results showed the variables that have a significant correlation with effectiveness of stakeholder communication for satisfaction in the process are characteristics of communication and database media includes the availability of infrastructure and facilities, and the amount of media communication, and variable of individual characteristics, it is the formal education, significant correlation for quality of information are social networks variables, there are density and closeness centrality.